Elaborasi Hukum Islam Dan Hukum Adat (Mediasi Konflik Suami Isteri Persukuan Piliong Dan Domo di Kenegerian Adat Airtiris) - Mawardi, Mawardi (Jurnal El-Thawalib, 2025)
Mediation has an important role in resolving or reconciling disputing parties, including domestic conflicts. In general, there are two forms of mediation, namely litigation mediation through the court, and non-litigation mediation or outside the court. Islam has also regulated the concept of mediation as stated in Q.S Annisa': 35. In the traditional land of Airtiris, there is a way of resolving household conflicts which has been carried out for generations through the involvement of Ninik Mamak in the mediation process carried out by both parties. This research is field research with a social juridical approach. Describe and explain how household conflicts are resolved between children and children and efforts to resolve disputes by ninik mamak in the Piliong and Domo tribes in Kenegerian Airtiris. Data sources include; primary data, namely, ninik mamak who became an actor in resolving the conflict using interviews in stages. Secondary data are books and research that are relevant to the study of factors that cause conflict and disputes in marriage. Tertiary data are enoclopedia and internet. Data was obtained by direct interviews with respondents. Through this article, we will describe the concept of Non-Litigation mediation in the form of customary mediation that applies in the Airtiris traditional land, especially in the Piliong and Domo tribes, which provides solutions in resolving household conflicts by involving Ninik Mamak as Hakam (peacemaker). It will also be aligned with the concept of "Hakamain" which is regulated in Islamic Law.